Application of Nanofluids for Machining Processes: A Comprehensive Review - Aoha Roohi Amin; Ahsan Ali; Hafiz Muhammad Ali (Nanomaterials, 2022)
According to the demand of the present world, as everything needs to be economically viable and environment-friendly, the same concept applies to machining operations such as drilling, milling, turning, and grinding. As these machining operations require different lubricants, nanofluids are used as lubricants according to the latest technology. This paper compares different nanofluids used in the same machining operations and studies their effects. The variation in the nanofluid is based on the type of the nanoparticle and base fluid used. These nanofluids improve the lubrication and cooling in the machining operations. They also aid in the improvement in the surface roughness, cutting forces, cutting temperature of the workpiece, and tool life in the overall process taking place. It is worth noting that nanofluids are more effective than simple lubricating agents. Even within the nanofluid, the hybrid type is the most dominating, and helps to obtain a maximum efficiency through certain machining processes.